The Clinical Point of View - Pulay, István; Tihanyi, Tibor F; Flautner, Lajos (JOP. Journal of the Pancreas)
Surgeons frequently find pancreatic head mass when operating. The obvious difficulty is to make the correct preoperative differential diagnosis between chronic pancreatitis and pancreatic tumor. The first step is to reach a diagnosis, with some certainty, prior to the operation. The second step in the case of a tumor is the accurate staging and deciding whether or not it is resectable. On the one hand, time and cost must be considered; on the other hand, the therapy must be decided. Obtaining information about the characteristics of the pancreatic disease (nature, size, exact location) and establishing the tissue diagnosis preoperatively may simplify the decision to operate and the operation itself. In the case of chronic pancreatitis, the aim of the operation is to eliminate pain and other symptoms, while in the case of cancer, the purpose is to remove the malignant tissue. In most patients, it is possible to identify the disease on the basis of previous examinations together with preoperative diagnostic techniques such as exploration, palpation and fine-needle aspiration biopsy. Chronic pancreatic head mass should be operated upon with Beger’s or Frey’s procedure while pancreatic head tumors should be treated by means of head resection with the aim of preserving the pylorus or the Whipple procedure may be used. When the diagnosis is in doubt, a radical approach is thought to be best. Our conclusion is that there is no diagnostic method capable of making a definitive differential diagnosis as to the nature of the pancreatic head mass. Further study is required as to the extent to which differential diagnosis should be investigated. Image: 1st Surgical Department, Semmelweis University. Budapest, Hungary.